Water Sustainability Assessment of Pune City: A Case Study of Selected Wards of Pune Municipal Corporation (International Journal of Food and Nutritional Sciences, 2023)
This paper surveys the main issues in the literature on residential water demand. Several issues and their objectives are analyzed. Then, the main contributions to the literature on residential water demand estimation, water loss, waste water treatment infrastructure, potential risk in water management are reviewed, with particular attention to variables, speciﬁcation model, data set, and the most common econometric problems. The paper concludes with comments on future water demands, water wastage and potential risk in water management.Pune municipal corporation areas are going to experience a continuous exponential built-up expansion in the coming years due to the rapid economic development. This shall lead to an unprecedented growth of the city in terms of population, which in turn shall increase the demand for housing and other civic amenities like water supply. A major chunk of the migrated population shall constitute of lower strata group, which would be forced to live in the slums due to demand-supply gap of housing in the city. Providing water connections to growing population of the slums could pose a challenge for the authorities, as it further adds to the burden of water resources already under pressure and an overall urban infrastructure.